2003
DOI: 10.1021/jp0349031
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Silver Nanoparticles under Protection of Poly(N-vinylpyrrolidone)

Abstract: A novel electrochemical method for size-controlled synthesis of spherical silver nanoparticles in aqueous phase was developed for the first time. In this method the poly(N-vinylpyrrolidone) (PVP) was used as the stabilizer for the silver clusters. PVP was found to greatly promote silver particle formation rate and significantly reduce silver deposition rate, thereby making monodispersed silver nanoparticles to be synthesized very convenient by means of electroreduction of the bulk silver ions. It is possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
263
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 494 publications
(275 citation statements)
references
References 48 publications
7
263
0
5
Order By: Relevance
“…According to our results, such an explanation was inadequate due to the fact that PVP with higher molecular weight can effectively prevent agglomeration of clusters or primary nanoparticles to form larger size. Yin et al [14] studied electrochemical synthesis of silver nanoparticles under protection of PVP with different molecular weight, particularly PVP K17, PVP K30 and PVP K90. They also reported that silver nanoparticles stabilised by PVP with higher molecular weight (PVP K30, PVP K90) exhibited a well-defined absorbance peak, whereas those obtained by stabilisation with lower molecular weight (PVP K17) did not show any peak under identical condition [14].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to our results, such an explanation was inadequate due to the fact that PVP with higher molecular weight can effectively prevent agglomeration of clusters or primary nanoparticles to form larger size. Yin et al [14] studied electrochemical synthesis of silver nanoparticles under protection of PVP with different molecular weight, particularly PVP K17, PVP K30 and PVP K90. They also reported that silver nanoparticles stabilised by PVP with higher molecular weight (PVP K30, PVP K90) exhibited a well-defined absorbance peak, whereas those obtained by stabilisation with lower molecular weight (PVP K17) did not show any peak under identical condition [14].…”
Section: Resultsmentioning
confidence: 99%
“…Yin et al [14] studied electrochemical synthesis of silver nanoparticles under protection of PVP with different molecular weight, particularly PVP K17, PVP K30 and PVP K90. They also reported that silver nanoparticles stabilised by PVP with higher molecular weight (PVP K30, PVP K90) exhibited a well-defined absorbance peak, whereas those obtained by stabilisation with lower molecular weight (PVP K17) did not show any peak under identical condition [14]. This meant that silver colloids obtained under protection of PVP K17 were of large silver particles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…where C o is the initial concentration of MB and C t the MB concentration after illumination time t. There have been several reports about the synthesis of metal nanoparticles by direct electroreduction of bulk metal ions in aqueous electrolytes [21][22][23]. The main difficulty is that electroreduction of metal ions involves a competition of two completely opposite cathode surface processes: the formation of metal nanoparticles and the metal electrodeposition on cathode [24].…”
Section: Photocatalytic Activitymentioning
confidence: 99%